Analisis Cita Rasa Dan Kualitas Pelayanan Pada UMKM Bubur Ayam Apolo - Herli Rizky Suherman; Ageng Saefudin Kanda (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study explores key aspects of the Apolo Chicken Porridge business through vendor interviews. The results show that focusing on ingredient quality, recipe innovation and taste consistency are the most important foundations in creating unique and attractive products. Effective service, responsiveness to customer input and strategic selling points also increase customer satisfaction. In conclusion, it is necessary to maintain product quality, improve service, respond to customers quickly and pay attention to the cleanliness and metode of the service area. At the same time, implementing loyalty programs and store evaluations can be additional strategies to strengthen the company's position in the culinary market.